Tanggung Jawab Pemilik Dalam Perjanjian Jual Beli Hasil Pohon - Fivanti Filberth Khoemarga; Merry Tjoanda; Sarah Selfina Kuahaty (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The sale and purchase agreement of tree products made by the community in Negeri Nolloth, Saparua District, Central Maluku Regency which is carried out between the seller and the buyer is an agreement in which one party binds himself to deliver an item, and the other party pays the promised price.Purposes of the Research: Therefore, this paper aims to analyze and discuss about sale and purchase agreement of tree products in Nolloth, Saparua District, Central Maluku RegencyMethods of the Research: This research uses normative juridical and sociological juridical research types with this type of research being descriptive analytical. The techniques for collecting legal materials are primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting is through literature study and then analyzed by means of description using qualitative methods.Result of the Research: The results obtained from this study are the sale and purchase agreement made orally by both parties is a legally valid agreement and the parties involved have fulfilled the requirements for the occurrence of an agreement so that it has become a responsibility and gives rise to rights and obligations to both parties. parties, but the seller cannot carry out its obligations and has no responsibility to the buyer after this agreement is implemented due to price increases so that the seller takes the proceeds from the tree that has been sold to the buyer which causes the buyer to suffer losses so the seller must be responsible under Article 1365 of the Law - Civil Law Act and, therefore, the legal consequences, the buyer can claim compensation from the seller. And also there is compensation that must be given to the buyer by the seller in the State of Nolloth, Saparua District, Central Maluku Regency.